LINGUISTIC ANALYSIS AND LEXICOGRAPHIC PRINCIPLES OF CARDIOLOGICAL TERMS IN ENGLISH AND UZBEK LANGUAGES - Zarrina Shavkatovna Yariyeva , Shokhsanam Rasulbekovna Tojiboyeva , Charos Alim kizi Adilova , Javlonbek Tohirjon ugli Abdurazzokov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research provides methods for translating medical terms with linguistic analysis and lexicographic principles based on cardiological vocabulary from English into Uzbek language.